PENGARUH DIVERSIFIKASI OPERASI, LEVERAGE, KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP MANAJEMEN LABA (STUDI EMPIRIS PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA(BEI) TAHUN 2014-2016) - Hidayah Rofany; Nasir Azwir; Desmiyawati Desmiyawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
Earnings information is part of financial statements that are used todetermine the performance and accountability of the company manager.Companies that have a high level of business complexity such as operationallydiversified companies, companies with high leverage are suspected of having theopportunity to take earnings management actions. To suppress the action ofearnings management, managerial oenership is indicated to reduce theoccurrence of earnings management and so does institutional ownership ofearnings management. This study aims to re-examine the effect to operatingdiversification, leverage, managerial ownership and institutional ownership onearnings management. The study was conducted at mining companies listed onthe Indonesia Stock Exchange in 2014-2016. The sampling. Analysis techniquewith multiple linear regression test. Based on the results of research with 33samples of observation companies, it is known that operating diversification hasno effect on earnings management, leverage does not effect earningsmanagement, managerial ownership does not effect eranings management andinstitutional ownership does not effect earnings managemen.Keyword : Earnings management, Operating Diversification, Leverage,Managerial Ownership and Institutional Ownership.